Efektivitas Aromaterapi Lemon terhadap Penurunan Mual Muntah pada Ibu Hamil Trimester I di Puskesmas Bies Kecamatan.Bies Kabupaten Aceh Tengah Tahun 2022 - Kartini Kartini; Nur Azizah; Ester Simanullang; Adelina Sembiring (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pregnancy is a physiological condition that causes physical and psychological changes, one of which is nausea and vomiting (emesis gravidarum), which often occurs in the first trimester. If left untreated, this condition can lead to nutritional disorders, dehydration, weight loss, and impact the health of the mother and fetus. Management can be carried out with pharmacological and non-pharmacological therapies, one of which is lemon aromatherapy, which is known to have a relaxing and refreshing effect and help reduce nausea symptoms. The purpose of this study was to determine the effectiveness of lemon aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester at the Bies Community Health Center, Bies District, Central Aceh Regency in 2022. The study used a quasi-experimental design with a one-group pretest-posttest design for pregnant women in the first trimester. Thirty respondents were selected using a purposive sampling technique. The research instrument used an observation sheet, and data analysis was performed using the Wilcoxon test. The results showed that before the intervention, the majority of respondents experienced severe nausea (53.3%) and moderate vomiting (50%). After receiving lemon aromatherapy, the majority of respondents experienced mild nausea (90%) and mild vomiting (93.3%). The statistical test results showed a p-value of 0.000 (p < 0.05), indicating a significant difference between before and after the intervention. The conclusion of this study is that lemon aromatherapy is effective in reducing nausea and vomiting in pregnant women in the first trimester. Lemon aromatherapy can be recommended as a safe, simple, and easy-to-implement non-pharmacological therapy alternative for treating emesis gravidarum.